Campus Entrepreneurship Service with Batik and Mathematical Ornaments - Hanna Arini Parhusip; Hindriyanto Dwi Purnomo; Didit Budi Nugroho; Istiarsih Saputri Sri Kawuryan (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
The popularization of mathematics and the downstream of research in entrepreneurship is still very rare in universities. Therefore, the purpose of community service is to create campus entrepreneurial activities that popularize mathematics as research downstream. The used method is by preparing object-identifying designs and making products that contain and use these designs in the form of various items known to the public such as batik, accessories, souvenirs, and ornaments. Activities for socialization are carried out by participating in various exhibitions, and competitions and providing training to school students. Likewise, social media such as Instagram, YouTube, and Shopee are also marketing media. In 2022, partnerships with several restaurants and shops were used to expand marketing. In the last 3 years, significant results have been obtained in popularizing mathematics due to community service activities in the form of campus entrepreneurship in the Campus Intellectual Product Business Development Program scheme from the Indonesian government. The public can easily find products called Batik Innovation Mathematics (Batima) and Ornament Decorative of Mathematics (Odema) in the campus area, social media, Malioboro Mall Jogjakarta, and several restaurants in Salatiga.